Communication Strategies Used by Papuan EFL Students - Andi Miftahul Maulidil Mursyid; Wira Kafryawan; Rahmawansyah Rahmawansyah (Metathesis: Journal of English Language, Literature, and Teaching, 2021)
To fill the absence of research in the context of communication strategies used by Papuan EFL students, this research would present and fill this knowledge gap. This research aimed to determine the types and their reasons of communication strategies used by Papuan EFL students. It applied qualitative study. The researcher used observation and interview as the research instruments. It was found that Papuan EFL employed fillers, code-switching, self-repetition, self-repair, asking for clarification, asking for confirmation, and direct appeal for help. The reasons why Papuan EFL students do those communication strategies because of thinking time, anxiety, nervousness, doubt, worriedness, hesitation, lack of knowledge, lack of vocabulary, grammatical errors, and self-confidence.